FAKTOR-FAKTO YANG BERHUBUNGAN DENGAN TINGKAT KEPATUHAN PERAWAT TERHADAP PENGGUNAAN ALAT PELINDUNG DIRI (APD) DI RSUP DR. KARIADI SEMARANG (Studi Kasus di Instalasi Rawat Inap Merak) - Salma Adilah Putri; Bagoes Widjanarko; Zahroh Shaluhiyah (Jurnal Kesehatan Masyarakat (Undip), 2018)
As a healthcare service, hospital can also be source of infection. An infection that exist in the hospital, known as Nosocomial infection, can occur in patient, health workers and person who came to the hospital. One of efforts to prevent nosocomial infection is by using personal protective equipments This research uses a quantitative with cross sectional approach. Analysis was done by using Chi square test. The populations of this research are nurses in Merak Inpatient Installation. This research use univariate and bivarite analysis. Based on the result of the research, it is know that 46,8% respondents was disobedience to use personal protective equipments according to procedure. The result of Chi-square test shows that education level of respondents (p=0,021) and  peer support (p=0,04) are significantly associated with the obedience level of nurses with the use of personal protective equipments behavior. While age of respondents (p=0,779), Work period of respondents (p=0,871), knowledge of respondents (p= 0,516), attitude of respondents (p=0,354), workload of respondents (p=0,059), regulation (p=0,207), facilities (p=1,000), and Supervision (p=0,642) are not significantly associated with obedience level of nurses to use personal protective equipments. The result of this research study suggests that strict sunction should be applied on the supervision toward non compliant nurse.